Indigenous Empowerment Through Community-Engaged Health Education Curriculum: Health Promotion in a Commercial Tobacco Cessation Campaign. (December 2021) - Newman Carroll, Sara; Mombourquette, Annie; Boxer, Majel; Williams, Rexine; Brewer, Sarah
Community-engaged classrooms offer advantages to both students and community-based organizations by creating an environment where students become agents of change and contribute to meeting communities' health needs. However, most community-engaged classroom research is done in high-income contexts in advanced curriculums with graduate students. This article explores a community-engaged classroom project at a minority- and indigenous-serving undergraduate institution, focusing on indigenous student empowerment. Commercial tobacco use prevention is of particular importance to indigenous contexts and resulted in a college policy change to reflect indigenous values. Students designed, implemented, and evaluated a tobacco product education campaign to effect change using a community-engaged approach. The educational activities included (1) understanding the tobacco context, (2) health communication course design, (3) forming key partnerships, (4) facilitating student activities through behind-the-scenes work, (5) designing and implementing a campaign, and (6) student growth and empowerment. We illustrate how academic and state partnerships can align interests in implementing public health policies and providing students with real-world public health communication and health equity experience.